Social care in the UK's four nations : between two paradigms - Needham, Catherine, 1974- (Book collections on Project MUSE., 2023)
The devolution of social care policy has led to key differences emerging between the UK's four care systems. This book presents research on the perspectives of social care policy makers within the UK's four care systems, concluding that when given equal capacity to reform, the systems in each nation may take radically different shapes.